The relationship of progestin contraception use with adequate breast milk production in breastfeeding mothers at the arungkeke public health center regency jeneponto 2023 - Juwita, Juwita; Asli, Kartika; Rahman, Nur Resti (Innovative Approaches in Health Science Journal, 2024)
Background: Based on data obtained from the Arungkeke Community Health Center in 2023, there were 2035 injectable birth control acceptors. Of the 1082 family planning acceptors, it was found that there were still acceptors who complained of problems with their breast milk production. This research aims to determine the relationship between contraceptive use and adequate breast milk production at the Arungkeke Community Health Center, Jeneponto Regency in 2023. Method: Researchers used an analytical survey research type with a cross sectional study approach. The sample was taken by purposive sampling with a total sample of 40 respondents using contraception. The independent variable is breastfeeding mothers who use contraception and the dependent variable is adequate breast milk production. Medical record data research instruments and checklists. Analysis using the Chi-square test ( The production of breast milk is not sufficient, while breastfeeding mothers who do not use contraception are 10 respondents (25%) whose breast milk production is not sufficient, there are 10 respondents (25%) and 0 (0%) who have sufficient production. Enough breast milk. Results: Chi-square test results (X) with a p-value of 0.000, which means p < α (0.05), which means Ho is rejected and Ha is accepted. Thus, there is a relationship between the use of contraception in breastfeeding mothers and the adequacy of breast milk production at the Arungkeke Community Health Center in 2023. Conclusion: It is hoped that health workers, especially midwives, will provide more optimal information and knowledge about contraception, especially regarding counseling on contraceptive choices